مناسبات جریان‌های شیعی عمان با حکومت و سایر مسلمانان - بیک زاده علیشاه, مجید; نواب, سیدابوالحسن; محمدی مظفر, محمد حسن (پژوهشنامه مذاهب اسلامی, 2024)
شیعیان عمان کلیتی واحد نیستند؛ برخی بلوچ، برخی خوجه، برخی بحرینی و شماری نیز عرب عمانی هستند. در هر کدام از این گروه‌ها شخصیت، هویت و تفکر جمعی خاصی ‌مشاهده می‌شود که همین امر سطوح متفاوتی از ادغام در جامعه میزبان را برای آنها رقم زده است؛ به این معنا که هرگونه تلاشی برای تقریب و نزدیک‌کردن مناسبات شیعیان عمان با دیگر مذاهب در گام اول مستلزم بر تمرکز خود شیعیان برای حذف مانع و چالش‌های موجود بین آنهاست. محدودیت‌های قانونی و ساختاری و استفاده حکومت از آنها برای مقابله با تحرکات و فعالیت‌های جدید، چالشی دیگر در این‌باره است. افزون بر آن هرگونه تلاش برای ساماندهی شیعیان عمان، ممکن است حساسیت حکومت عمان را برانگیزد که روابط حسنه‌ای با جمهوری اسلامی دارد. این پژوهش با استفاده از دو روش مطالعۀ کتابخانه‌ای و مصاحبه با یکی از کارشناسان ارشد مسائل عمان، به بررسی بیشتر جوانب حضور شیعیان در جامعه عمان می‌پردازد و رابطه آنها را با اباضیه بررسی می‌کند که بیشتر جامعه عمان را تشکیل می‌دهند، نظام حکومتی عمان را در اختیار دارند و اشتراک‌های بسیاری نیز با شیعیان دارند. این نوشتار اباضیه عمان را گزینه مناسب تقریب و دارای قابلیت‌های لازم برای دیپلماسی فرهنگی جمهوری اسلامی در نظر می‌گیرد.
Keywords: Chiisme – Oman; Tolérance religieuse – Oman

Religious-Ethnic Structure of the Sultanate of Oman - Abzhapparova, Bibikhadisha (Kazakhstan Oriental Studies, 2024)
The Sultanate of Oman is a unique state of the Persian Gulf, its population lives in a rapidly developing and prosperous society. The novelty of the article consist  in the fact that it studied  the way of life, traditions, religions and the history of settlement of various ethnic groups in the life of the Sultanate of Oman, as well as the peculiarities of local languages in the country. The article examines the lifestyle, traditions, religions of various ethnic groups rooted in the life of this country, as well as the history of their arrival and settlement in Oman. The sites of settlement of large ethnic groups such as Balochis, Bahais, Luati, Zanzibari and Indians were studied, and how they assimilated into society. The article analyzes how some historical events and historical aspects of the Sultanate of Oman influenced the ethnic structure in it. The practical significance of the article lies in the fact that it will help researchers dealing with the countries of the Persian Gulf, Oriental studies and international relations. The article examines the variants of the origin of the word "Oman", the explanations left by the researchers. It was discussed which religions the people of Oman profess, which religion is more widespread in which region. We analyzed the history, lifestyle, and characteristics of the tribes and ethnic groups known in this country, where they mainly live. Attention was drawn to the country's special support for religious tolerance and peace in society.  In the methodology of writing the article, methods of analysis-synthesis, deduction, formalization, open electronic sources, works of foreign and domestic scientists who studied this topic were used.
Number: 3
Keywords: Tolérance religieuse – Oman

Tolerance as a Legitimation Strategy in Oman’s Political Discourse: From Religious to Foreign Policy Principle - Daga, Giulia (The International Spectator, 2024)
In the past few decades, the concept of tolerance has gained a central place in Oman’s political discourse and foreign policy. It is often attributed to the country’s national identity, which in turn is interpreted as deriving from Oman’s Ibadi tradition, the cosmopolitan character of its maritime history and its strategic geographic location. Despite greater attention being paid to the constructive nature of Oman’s identity, including its connection with Ibadism, however, a careful reflection on how the concept of tolerance developed from a religious to a foreign policy principle is still missing. A Discourse-Historical analysis of speeches directed towards a domestic and international audience highlights how the political discourse on tolerance, by reinforcing identity-engineering efforts, supported the Omani government’s legitimation and status-seeking purposes at home and abroad.
_eprint: https://doi.org/10.1080/03932729.2024.2381198
Keywords: Tolérance religieuse – Oman